Application of the micellar-enhanced ultrafiltration combined with the activated-carbon-fiber filtration for nikel and zinc removal from aqueous solution - Bundit Channarong; Shipin, Oleg V.; Jutamaad Satayavivad; Chongrak Polprasert; Babel, Mukand Singh; Chulabhorn Research Institute; Mahidol University; Royal Thai GovernmentFellowship (Pathum Thani : Asian Institute of Technology, 2014)
The micellar-enhanced ultrafiltration (MEUF) combined with activated carbon fiber filtration (ACF) for nickel, zinc, and sodium dodecyl sulfate (SDS) removalfrom aqueous solution was studied toidentify the effect of molecular weight cutoff (MWCO) andmolarratio between surfactant and heavy metalson the removal of nickel, zinc and SDSwith a view to designing an effective process for removal of heavy metalsconcomitant with SDS removal (the latter being necessary for the high heavy metal removal).It was found that the efficienciesof Ni(II) removal from Nickel-SDS solution by the MEUF system (with 100 kDa membrane)were upto96.5%, and the efficiencies of Ni(II) and SDS removal MEUF-ACF hybrid process were up to 99.3% and 99.8%, respectively.The efficienciesof Zn(II) removal from Zinc-SDS solution by the MEUF system (with 100 kDa membrane) wereup to 97.6%, and theefficiencies of Zn(II) and SDS removal by the MEUF-ACF hybrid process were up to 99.9% and 92.5%, respectively.The pattern was similar for simultaneous Ni(II), Zn(II) and SDS removalby the hybrid process.However in case of a larger MWCO membrane efficiencies of Ni(II) removal from Nickel-zinc-SDS solution by the MEUF system (with 300 kDa membrane) and MEUF-ACF hybrid process were up to 90.7% and 99.3%, respectively; the efficiencies of Zn(II)removal from Nickel-zinc-SDS solution by the MEUF system (with 300 kDa membrane) and MEUF-ACF hybrid process were up to 90.1% and 99.9%, respectively.The MEUF system with very large MWCO membrane can be operated by using a constant permeate flow rate with the high removal efficiency. In addition, low inlet pressure of 0.7 bar was found to be optimalfor the ACF system of the hybrid process with 100 kDa membrane.In terms of mechanisms underlying the MEUF system it is suggested that metal and SDS removal by thesystem was initially due topore narrowingby the surfactant adsorption at the wall of membrane pore, and then due tothe formation of the concentration polarization (CP) of micelles near the boundary of membrane. Consequentlythe CP of micelles led to the formation of a compact-micelle layer (CML) on the membrane surface that acted as a secondary membrane.Therefore, the formation of the concentration polarization of micelles and compact-micelle layer resulted in high efficiencies of removal of micelles and metal-micelle complexes. Moreover,it issuggested that the formation of metal-micelle complexes in the bulk solution could enhance to form a high dense compact-micelle layer (HD-CML) at the membrane surface and resulted in very high metal removal. However, the mixing between free micelles and metal-micelle complexeson the membrane surface ledto form a medium dense compact-micelle layer (MD-CML). It appearsfrom the results that the formation ofconcentration polarization of micelles with a compact-micelle layer playsa major role in the rejection of free micelles and metal-micelle complexes by the MEUF system.Overall, it can be concluded that the ACF system was able to perform a high quality removal after the MEUF system which can ensure a constant permeate flow rateallowing for ease of connection with potential downstream processes.
A dissertation submitted in partialfulfillment of the requirementsfor the degree of Doctor of Engineeringin Environmental Engineering and ManagementInter-University Program on Environmental Toxicology, Technology and Management
Thesis (Ph.D.) - Asian Institute of Technology - Chulabhorn Research Institute - Mahidol University, 2014
Keywords: Sewage -- Purification -- Heavy metals removal; Zinc; Nikel